2008
DOI: 10.1210/en.2008-0207
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Amino Acid Residues in a Thyrotropin Receptor Monoclonal Antibody Epitope Provides Insight into Its Inverse Agonist and Antagonist Properties

Abstract: CS-17 is a murine monoclonal antibody to the human TSH receptor (TSHR) with both inverse agonist and antagonist properties. Thus, in the absence of ligand, CS-17 reduces constitutive TSHR cAMP generation and also competes for TSH binding to the receptor. The present data indicate that for both of these functions, the monovalent CS-17 Fab (50 kDa) behaves identically to the intact, divalent IgG molecule (150 kDa). The surprising observation that CS-17 competes for TSH binding to the human but not porcine TSHR e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
2
16
1
Order By: Relevance
“…19,20 The results showed that TSH-stimulated production of cAMP in L-02 cells and human primary hepatocytes cultured in the presence of CS-17 was significantly lower than that in cells cultured without CS-17 (P < 0.001) (Fig. 3A, upper).…”
Section: Resultsmentioning
confidence: 96%
“…19,20 The results showed that TSH-stimulated production of cAMP in L-02 cells and human primary hepatocytes cultured in the presence of CS-17 was significantly lower than that in cells cultured without CS-17 (P < 0.001) (Fig. 3A, upper).…”
Section: Resultsmentioning
confidence: 96%
“…As detected by ELISA, diethylaminoethyl (DEAE) chromatography accomplished sufficient separation for the HR from the bulk of medium proteins (primarily albumin) to permit subsequent anti-5His affinity purification followed by Superdex-75 gel filtration. However, because of total overlap between the TSHR ECD and medium proteins, we turned to affinity chromatography with CS-17, a murine mAb primarily to the LRD (30,31), linked to CNBrSepharose 4B (Sigma-Aldrich).…”
Section: Protein Purificationmentioning
confidence: 99%
“…Anion exchange chromatography at various pH levels failed to provide an initial, relatively selective capture of the ECD, with complete overlap in elution of the ECD as detected by ELISA and the bulk of serum proteins in the culture medium (data not shown). Finally, we generated an affinity column with TSHR mAb CS-17 whose epitope is primarily to the LRD (31). Fortunately, as determined by PAGE, this mAb captured the TSHR ECD from conditioned culture medium in a single step to more than 90% purity with a yield of 0.1-0.3 mg/L in different preparations, typically approximately 0.2 mg/L ( Figure 5).…”
Section: Purification Of the Tshr Ecd And Hrsmentioning
confidence: 99%
“…Confirmation using a second control mAb that deletion of TSHR N-terminal disulfide-linked loop 1 reduces the number of cell surface receptors detected by M22. The experiments were identical to those described in Figure 2 using CHO cells stably expressing TSHR-ECD-GPI and D22-30 TSHR-ECD-GPI except for the use of control murine mAb CS-17 (A) whose epitope lies within the junctional region between the TSHR LRD and hinge regions, far downstream of the N-terminal cysteine cluster (24,25). (B) Flow cytometry with M22 using aliquots in the same experiment of cells used for CS-17.…”
Section: Functional Studies With the Tsh Holoreceptormentioning
confidence: 99%